Association between types of antihypertensive medication and the risk of atrial fibrillation: a nationwide population study - Choi, JungMin; Lee, So-Ryoung; Choi, Eue-Keun; Lee, Kyung-Yeon; Ahn, Hyo-Jeong; Kwon, Soonil; Kim, Bongseong; Han, Kyung-Do; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2024)
Background Patients with hypertension are at a high risk of atrial fibrillation (AF). Recent research has indicated the varying effects of antihypertensive medications on developing AF. Objectives We investigated the relationship between different types of antihypertensive medications and the risk of AF occurrence. Methods We analyzed data from 113,582 subjects with national health screening examinations between 2009 and 2014. The study population was categorized according to antihypertensive medication type. The primary outcome was the incidence of AF. Results Among 113,582 subjects (mean age 59.4 ± 12.0 years, 46.7% men), 93,557 received monotherapy [angiotensin receptor blockers (ARB), angiotensin-converting enzyme inhibitors (ACEi), beta-blockers, calcium channel blockers (CCB), or diuretics], while 34,590 received combination therapy (ARB/beta-blockers, ARB/CCB, ARB/diuretics, or ARB/CCB/diuretics). During a mean follow-up duration of 7.6 ± 2.1 years, 3.9% of patients were newly diagnosed with AF. In monotherapy, ACEi and CCB had similar AF risks as ARB, while beta-blockers and diuretics showed higher AF risks than ARB. In combination therapy, ARBs/CCBs and ARBs/diuretics had the lowest AF risk, whereas ARBs/beta-blockers had the highest compared to ARB/CCB. Among the specific ARBs, the AF risk varied insignificantly, except for telmisartan and candesartan. Conclusions In hypertensive patients receiving monotherapy, ACEi and CCB showed a similar AF risk as ARBs, while beta-blockers and diuretics were associated with a higher risk. Among those receiving combination therapy, ARBs/CCBs and ARBs/diuretics had the lowest AF risk, whereas ARBs/beta-blockers showed the highest risk. Various types of ARBs have different associations with AF risk.